The Anatomical Architecture of the Junction between the Great Cerebral Vein and the Straight Sinus in Correlation to the Physiological and Biochemical Impact on Multiple Sclerosis Subtypes and Disease Progression (A Review Article) - WJ, Cobb; ST, Cook; MA, Gardenhire; JC, Harrington (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Multiple Sclerosis (MS) is a debilitating autoimmune disorder, characterized by damage to the white matter of the central nervous system. Studies suggest a relationship between impaired cerebral venous blood flow and progressive destruction of white matter in the CNS. Altered cerebral venous architecture is a possible mechanism that may contribute to a compromised venous blood flow pattern in MS patients. Natural variations at junction located between the great cerebral vein (GCV) and the straight sinus (Ss) located within the cerebral venous drainage system can potentially exacerbate MS progression. Recent data indicates that abnormal cerebral venous hemodynamics contributes to the pathophysiology observed in MS through an unknown mechanism that increases hydraulic resistance.